Analisis Penegakan Hukum terhadap Perusahaan Pers yang Tidak Berbadan Hukum - Siagian, Agus; Riza, Khairul; Lubis, Irpan Husein (Kajian Ilmiah Hukum dan Kenegaraan, 2022)
Purpose: To find out law enforcement against press companies that are not legally incorporated, find out the obstacles and efforts made against law enforcement for press companies that are not legally incorporated. Method: The method used is empirical legal research, by conducting observational research in the field by seeking information through interviews. And also supported by normative research with literature studies. Result: The results of the study show that law enforcement against press companies that are not legal entities in Batam City has not run optimally criminally, civilly or in state administration, there are still many press companies that are not legally incorporated working to disseminate information on news coverage in Batam City. Obstacles in carrying out law enforcement for press companies that are not legal entities in Batam City are weak supervision from the authorities, lack of outreach from the press council, the lack of strict sanctions imposed by the press council, and no party reporting. Efforts are being made to overcome these obstacles, namely, increasing supervision from the press council, increasing socialization of the negative impacts of press companies that are not incorporated, increasing the work function of the press council with journalist organizations, and increasing the performance of journalist organizations in controlling journalists who work in under an unincorporated press company.